2012
DOI: 10.21273/hortsci.47.4.527
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Effect on Seed Germination and Growth of Two Warm-season Native Grass Species

Abstract: Salinity tolerance of five buffalograss [Buchloe dactyloides (Nutt.) Englem.] cultivars (Texoka, Cody, Bison, Sharp's Improved II, and Bowie) and three blue grama [Bouteloua gracilis (Willd. ex Kunth) Lag. ex Griffiths] ecotypes (‘Lovington’, ‘Hachita’, and ‘Bad River’) was determined during in vitro seed germination and vegetative growth in a hydroponic system. Seeds were germinated on 0.6% agar medium supplemented with NaCl at 0, 5, 10, 15, and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…4A). It was not surprising to see this result because previous studies have observed that increasing salinity stress inhibited plant growth and development of ornamental grasses significantly (Alvarez, 2006;LeCompte et al, 2016;Zhang et al, 2012).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…4A). It was not surprising to see this result because previous studies have observed that increasing salinity stress inhibited plant growth and development of ornamental grasses significantly (Alvarez, 2006;LeCompte et al, 2016;Zhang et al, 2012).…”
Section: Resultsmentioning
confidence: 70%
“…ex Kunth) Lag. ex Griffiths (blue grama) has moderate tolerance to salinity when grown at a saturated soil extract (EC e ) of 4 to 8 dS • m -1 (Kratsch et al, 2008), and its salt tolerance varies within ecotypes and is greater at the germination stage than the mature stage (Zhang et al, 2012). P. alopecuroides 'Hameln' is slightly more tolerant to salt spray than M. sinensis 'Gracillimus' (Alvarez, 2006).…”
mentioning
confidence: 99%
“…Texoka were used in this experiment. Salinity tolerance of the grasses were determined in the previous studies (17,18), except tall fescue cv. Stonewall.…”
Section: Salinity Waterlogging and Their Combined Effectsmentioning
confidence: 99%
“…The sub‐plot factor was the four turfgrass species. Within each species, data were expressed as percent of the control to avoid genetic differences in seed size and seedling vigor (17). Data were subjected to analysis of variance using PROC GLM (SAS Institute Inc., Cary, NC) and means were separated with Fisher's protected least significant difference at P ≤ 0.05.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…The discrepancy between our study and the previous findings might be the result of the different cultivars evaluated in the studies or differences in growth stages. Because salinity tolerances vary during plant growth stages Zhang et al, 2012), we speculate that drought tolerance may also vary in growth stages as well. Unfortunately, growth stage was not defined by Beard (1973).…”
Section: Discussionmentioning
confidence: 99%